Scope of Homoeopathy in Peritonsillar Abscess (Advancements in Homeopathic Research, 2022)
A Peritonsillar abscess is also known as Quinsy. It  is an accumulation of pus behind the palatine tonsil  due to an infection. Precisely, it is a collection of pus  between the fibrous capsule of the tonsil, usually at  the upper pole & the superior constrictor muscles of  pharynx. The signs & symptoms of quinsy include  fever, throat pain, trouble in opening mouth, redness,  swelling and change in the voice. Pain is usually  worse on one side. The complications may include  blockage of the airway or aspiration pneumonitis.  The conventional treatment is done for removing the  pus by incision & drainage along with medications  for swelling & pain management. The homeopathic  line of treatment depends on the actual state of the  condition. Homeopathic medicines can be used  in mild to moderate cases of peritonsillar abscess  successfully as see through this research study. In  this study, 46 cases of peritonsillar abscess of age  group between 5 to 80 years were included. After  going through the results, it is observed that the  peritonsillar abscess can be treated successfully by  Homoeopathy. The scope of Homoeopathy in the  treatment of peritonsillar abscess is excellent and  shows high success rate of 44 out of 46 patients  responding successfully to the Homoeopathic  treatment with no signs of recurrence in near future.  The outstanding Homoeopathic remedies in the  treatment of peritonsillar abscess were found to  be mostly Hepar Sulph & Merc Sol along with  Calc Carb, Baryta Carb and Phytolacca. All that is  required in the treatment of peritonsillar abscess is  quick selection of right remedy and right dose for  the instant relief rationally. Hence we can rightly  claim that by proper Homoeopathic treatment we  can make the world better for the future generation.  This research paper will certainly help the health  professionals to overcome such problems of surgical  cases and consider the benefits of the facts in scope  of Homoeopathy in peritonsillar abscess.
Keywords: Peritonsillar abscess; Quinsy; Homoeopathy